Application sequence modulates microbiome composition, plant growth and apple replant disease control efficiency upon integration of anaerobic soil disinfestation and mustard seed meal amendment. (June 2020) - Mazzola, Mark; Graham, Danielle; Wang, Likun; Leisso, Rachel; Hewavitharana, Shashika S.
Abstract: Anaerobic soil disinfestation (ASD) and mustard seed meal (MSM) amendments can provide effective control of soil-borne diseases including apple replant disease. These measures rely on both chemical and biological modes of action to yield effective disease control and their integration may prove beneficial or, alternatively, deleterious to overall treatment efficiency when applied in concert. Potential outcomes of integrating ASD with MSM amendments were assessed by determining the effect of treatment application sequence and ASD carbon source on generation of allyl isothiocyanate (AITC) derived from Brassica juncea seed meal, structure of the rhizosphere and soil microbiome, control of apple replant pathogens, and plant growth. In bioassays conducted using 'Gala' apple seedlings, application of ASD or MSM treatments independently was as effective or superior to all integrated treatments for the control of replant pathogens. Application of ASD prior to MSM amendment diminished the yield of AITC attained in response to soil incorporation of the Brassica juncea:Sinapis alba seed meal. Treatment application sequence had significant effect on structure of the bulk soil fungal and bacterial community. Correspondingly, treatment application sequence significantly altered plant growth performance when orchard grass was utilized as the ASD carbon input. At harvest, rhizosphere fungal but not bacterial community composition was significantly altered in treated soil relative to the control, and sequence of treatment application had significant effect on rhizosphere fungal community structure. Failure of integrated treatments to enhance overall replant disease control may have resulted from many factors including reduced generation of active metabolites, diminished activity of mechanisms functional in pathogen suppression, or the elevated accumulation and retention of phytotoxic chemistries, the latter which would require extended plant back periods to circumvent. The findings indicate that under the experimental conditions employed, integration of ASD with MSM amendment is unlikely to yield additive or synergistic effects on apple replant disease control. Highlights: ASD and MSM application sequence influences soil microbiome composition. ASD applied prior to MSM reduces allyl isothiocyanate yield in treated soil. ASD and MSM applied independently control apple replant pathogens. Integration of the two methods does not enhance replant disease control.